Effectiveness of Midwifery Care for Family Planning (KB) Acceptors with IUD (Intrauterine Device): Study in Kayu Kul Village, Pegasing, Central Aceh, Indonesia - Hidayana; Irdayani; MS, Sri Wahyuni (Community Medicine and Education Journal, 2024)
Family planning (KB) is one of the Indonesian government's priority programs to control the rate of population growth. IUD (Intrauterine Device) is an effective and popular family planning method in Indonesia. Quality midwifery care is important to ensure successful IUD use and increase acceptor satisfaction. This study aims to analyze the effectiveness of midwifery care for family planning acceptors with IUDs in Kayu Kul Village, Pegasing, Central Aceh, Indonesia. This study used a cross-sectional observational design involving family planning acceptors with IUDs in Kayu Kul Village, Pegasing, Central Aceh, Indonesia. Data was collected through structured interviews and observations of midwifery care provided to acceptors. Data were analyzed using univariate and bivariate analysis with the Chi-square test. The results showed that the majority of family planning acceptors with IUDs (80%) received effective midwifery care. Effective midwifery care includes: complete health screening, comprehensive education about IUD use, counseling about IUD side effects and complications, and regular monitoring of IUD use. Acceptors who received effective midwifery care had a higher level of satisfaction (90%) compared to acceptors who did not receive effective midwifery care (60%). Effective midwifery care has been proven to increase family planning acceptor satisfaction with the IUD. Therefore, it is important to improve the quality of midwifery care at Health Centers to ensure successful use of IUDs and increase acceptor satisfaction.